Tourism Development Strategies During Pandemic of Covid-19 - Rita Rahmawati; Dede Syahrudin; Novel Anak Lydon (Indonesian Journal of Social Research (IJSR), 2023)
The research was motivated by the declining condition of tourism in Indonesia due to Covid-19, but it has the potential to develop further. Therefore, this study aims to describe the prospect and strategies for developing tourism during COVID-19. This research used a qualitative approach with descriptive methods by taking the case of tourism in Sukabumi Regency, Indonesia. Data were collected by observation and in-depth interviews by taking government and community leaders as key informants. Furthermore, informants who understand tourism development were selected through purposive and snowballing sampling techniques: related government (n=7) and the community (n=20). Data was also collected in focus group discussions to identify problems through swot analysis and formulate tourism development strategies. The study results show data that during the Covid-19 pandemic, tourism potential has increased in variety and innovation due to encouragement from the government and community efforts to independently develop their area as a tourist attraction when tourist visits are closed. The recommendation of this research is to make a grand design strategy for tourism development, developing and strengthening tourism institutions at the government and community levels, infrastructure development, and sustainable collaborative management.